Emotional Responses and Self-Protective Behavior Within Days of the COVID-19 Outbreak: The Promoting Role of Information Credibility - Lep, Žan; Babnik, Katarina; Hacin Beyazoglu, Kaja (Frontiers in Psychology, 2020)
Due to changes in the information environment since the last global epidemic, high WHO officials have spoken about the need to fight not only the current COVID-19 pandemic, but also the related infodemic. We thus explored how people search for information, how they perceive its credibility and how all this relates to their engagement in self-protective behaviors in the crucial period right after the onset of COVID-19 epidemic. The online questionnaire was circulated within 48 hours after the first case of COVID-19 was confirmed in Slovenia. We gathered information on participants’ demographics, perception of the situation, their emotional and behavioral responses to the situation (i.e., self-protective behavior), perceived subjective knowledge, perceived credibility of different sources of information, and their level of trust. We looked into the relationships between perceived credibility and trust, and self-protective behavior of 1,718 participants and found that mass media, social media and officials received relatively low levels of trust. Conversely, medical professionals and scientists were deemed the most credible. The perceived credibility of received information was linked with lower levels of negative emotional responses, but also with higher adherence to much needed self-protective measures, which aim to contain the spread of the disease. While results might vary between societies with different levels of trust in relevant governmental and professional institutions, and while variances in self-protective behavior scores explained by our model are modest, even a small increase in self-protective behavior could go a long way in viral epidemics like the one we are facing today.